2009
DOI: 10.1590/s0103-84782009000700010
|View full text |Cite
|
Sign up to set email alerts
|

Mild temperatures on bud breaking dormancy in peaches

Abstract: The search for low chill cultivars for peach production in areas with low chill accumulation (temperatures below 7.2°C) has stimulated studies about the higher temperatures effects on low chill cultivars. The objective of this research was to evaluate the influence of mild temperatures on flowering and leafing of 'Turmalina' and 'Ágata' cultivars with low and medium low chilling requirements, respectively. Plants obtained by grafting flower twigs in the autumn, after the grafting, were submitted to chilling tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 15 publications
1
11
0
2
Order By: Relevance
“…Putti et al (2003b), using single node cutting biological test, also observed that the effectiveness of temperature to overcome dormancy varies among apple cultivars, where cultivars with lower chilling requirement have effective temperatures higher than cultivars with higher chilling requirement. The same response was obtained by Chavarria et al (2009), using the grafted twigs methodology in peach trees, where the temperatures of 15ºC during winter promoted satisfactory percentage of budbreak and flowering in low chill cultivars, such as 'Turmalina' cultivar.…”
Section: Resultssupporting
confidence: 65%
See 2 more Smart Citations
“…Putti et al (2003b), using single node cutting biological test, also observed that the effectiveness of temperature to overcome dormancy varies among apple cultivars, where cultivars with lower chilling requirement have effective temperatures higher than cultivars with higher chilling requirement. The same response was obtained by Chavarria et al (2009), using the grafted twigs methodology in peach trees, where the temperatures of 15ºC during winter promoted satisfactory percentage of budbreak and flowering in low chill cultivars, such as 'Turmalina' cultivar.…”
Section: Resultssupporting
confidence: 65%
“…According to Petri and Leite (2004), trees in mild winter climates have terminal growth stimulated, which inhibits the budbreak in axillary buds. Chavarria et al (2009), Wagner Junior et al (2006 did not reported problems related to budbreak limited in axillary buds with the method using grafted twigs in peach, obtaining budbreak percentage over 50% in the highest chilling exposure tested. The low percentage of budbreak in both apple cultivars in the method using grafted twigs may be associated to the high apical dominance characteristic of apples trees.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…In this figure Hawerroth et al (2013) found that this temperature is the most efficient in an early variety of apple trees under controlled temperature conditions (5, 10 and 15 o C). Under subtropical climate conditions, some peach cultivars break their dormancy very easily, and this may be due to superficial dormancy or lack of endodormancy (CHAVARRIA et al, 2009;HRUY et al, 2013;SCARIOTTO et al, 2013). Observing the behavior of group 2 varieties, an opposite result in relation to many models used worldwide was observed, which consider a sequential influence of temperatures on dormancy.…”
Section: Introductionmentioning
confidence: 99%
“…Para que se inicie novo ciclo vegetativo na primavera em condições naturais, é necessário que as plantas sejam expostas a um período em que as temperaturas sejam inferiores a 7,2 °C durante o inverno e este período é variável em função da espécie (Putti et al, 2003). No entanto, Chavarria et al (2009) demonstraram que temperaturas abaixo de 12 ºC são efetivas na superação da endodormência em cultivares de pessegueiro de baixa necessidade de frio.…”
Section: Introductionunclassified